Identification of Annexin A2 as a target protein for plant alkaloid matrine. Issue 36 (21st April 2017) - Wang, Dongyao; Cao, Yan; Zheng, Leyi; Lv, Diya; Chen, Langdong; Xing, Xinrui; Zhu, Zhenyu; Li, Xiaoyu; Chai, Yifeng
Abstract : The cellular target of matrine is identified. Abstract : Matrine is a plant alkaloid and a major active component in the Chinese medical herb Sophora flavescens . Matrine has shown potent anti-cancer activities but its molecular target(s) and mechanism are still unknown. Using the photo-affinity labeling approach, for the first time, Annexin A2 was identified as a direct-binding target of matrine in cancer cells.